Pakistan Economic Update, June 2011 - World Bank (Washington, DC, 2017)
For the last three years, Pakistan has been making efforts to revive strong and sustained growth. The economy was badly destabilized by the turmoil in the international commodity and financial markets in 2007-2008 and the lack of adequate domestic policy responses to manage those external shocks. The task of stabilizing the economy and reviving the economic recovery has been made difficult by an adverse security situation and domestic politics that has prevented the government from taking timely required, but difficult, stabilization measures. The devastating floods in July-August last year and the recent increase in international oil and food prices have exacerbated the problem. In addition, Pakistan continues to face significant political challenges in achieving durable development. The domestic security situation as a result of campaign against terrorism is a direct and indirect tax on the costs of economic activity and the achievement of the kinds of social stability required to promote a supportive environment for businesses.